Bounded solvability of mixed-type functional differential operators for first order - (:unkn) unknown (Texas State University - San Marcos, 2016)
In this article, we study all boundedly solvable extensions generated by linear mixed-type (forward-backward) functional differential-operator expressions of first order in the Hilbert space of vector-functions on a finite interval. Our main tools are methods of operator theory. Also we study the structure of the spectrum of these extensions. © 2016 Texas State University.
Keywords: Bounded solvable operator; Mixed-type functional differential expression; Spectrum